Preliminary investigation of poor nut yield performance of Sri Lanka Green Dwarf in the coconut belt of South - Western Ghana - E. Andoh-Mensah; R. Philippe; J. Owusu-Nipah (International Coconut Community Journal, 2007)
A lethal yellowing disease known locally as Cape Saint Paul Wilt Disease (CSPWD) has brought the coconut industry in Ghana under a serious threat due to its devastating effect. The Sri Lanka Green Dwarf (SGD) is so far the only coconut ecotype identified to have shown least susceptibility to the disease. However, in the coconut belt of South - Western Ghana, where the SGD is mainly found, this coconut ecotype has a general problem of low nut yield and wide variability in nut load. A phenomenon that does not auger well for any hybridization programme involving the ecotype. Consequently, between August 2003 and March 2004 an investigation was carried out into the problem of low yield and large variability of nut load in the SGD. Soil and leaf samples were taken from SGD plots in South - Western Ghana and analysed. Nut count was carried out to estimate annual nut load per tree. Pest survey and identification were also done. Results indicated nutritional/soil factors especially K deficiency or pest damage particularly due to Pseudoptheraptus devastans (coconut bug) or a combination of the two as being largely responsible for the low yield and wide variability in nut load. Oecophylla longinoda (red ant) was confirmed as the natural enemy of the coconut bug during the study.